PENYIMPANGAN MAKSIM KESANTUNAN PADA FILM KARTUN SPONGEBOB SQUAREPANTS KARYA STEPHEN HILLENBURG (KAJIAN PRAGMATIK) - Shofia Cahyani Putri (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This study aims to describe the deviance of politeness maxims that occur in the SpongebobSquarepants cartoon film that is carried out from January to May 2018. The focus used in this study is the deviation of maxim of language politeness derived from Leech's theory include: deviation of maximal wisdom, deviation maxim of generosity, deviation from maxims of appreciation, deviation from the maxim of simplicity, deviation from maximization of consent, and deviation from maximization of conclusions. With the sub focus of politeness scale which includes the scale of loss and profit, choice scale, scale of non-continuity, authority scale, and social distance scale. The method used in this study uses a qualitative descriptive method with content analysis techniques. The object of this study was the cartoon film SpongebobSquarepants by Stephen Hillenburg. In this study, data were obtained on the cartoon SpongebobSquarepants in three episodes, Pineapple Fever, Sandy, Spongebob, and The Worm, and SquidwardThe Unfriendly Ghost, which consisted of 209 pairs of speeches. Maximum politeness deviation is 138 pairs of utterances (66.02%), while fulfillment of politeness maxim is found as many as 71 pairs of utterances (33.98%). Found 1 data maximal deviations (0.72%), 5 data maximal maximal deviations (3.62%), 46 maximal awards deviations (33.3%), 26 data maximization simplicity (18.84 %), deviation of agreement maximization as much as 61 data (44.3%), and deviation of maximization of conclusions as much as 17 data (12.6%). Then obtained politeness scale of 209 pairs of utterances. 138 fulfills politeness and 71 pairs of utterances fulfill impoliteness. The results of this study concluded that the deviations in maxim of politeness speak more than the fulfillment of politeness maxim in the cartoon film SpongebobSquarepants. In this study can be implicated in Indonesian language learning, namely learning in the text of the discussion class IX junior high school. Keywords: politeness maxim, cartoon film, Spongebob Squarepants Abstrak Penelitian ini bertujuan untuk mendeskripsikan penyimpangan maksim kesantunan yang terjadi di dalam film kartun Spongebob Squarepants yang dilakukan pada bulan Januari sampai dengan bulan Mei 2018. Fokus yang digunakan dalam penelitian ini adalah penyimpangan maksim kesantunan berbahasa yang diturunkan dari teori Leech meliputi: penyimpangan maksim kebijaksanaan, penyimpangan maksim kedermawanan, penyimpangan maksim penghargaan, penyimpangan maksim kesederhanaan, penyimpangan maksim permufakatan, dan penyimpangan maksim kesimpatisan. Dengan sub fokus skala kesantunan yang meliputi skala kerugian dan keuntungan, skala pilihan, skala ketidaklangsungan, skala keotoritasan, dan skala jarak sosial. Metode yang digunakan dalam penelitian ini menggunakan metode deskriptif kualitatif dengan teknik analisis isi. Objek penelitian ini adalah film kartun Spongebob Squarepants karya Stephen Hillenburg. Dalam penelitian ini didapatkan data pada film kartun Spongebob Squarepants dalam tiga episode yaitu Pineapple Fever, Sandy, Spongebob, and The Worm, dan Squidward The Unfriendly Ghost sebanyak 209 pasangan ujaran. Penyimpangan maksim kesantunan sebanyak 138 pasangan ujaran (66,02%), sedangkan pemenuhan maksim kesantunan ditemukan sebanyak 71 pasangan ujaran (33,98%). Ditemukan penyimpangan maksim kebijaksanaan sebanyak 1 data (0,72%), penyimpangan maksim kedermawanan sebanyak 5 data (3,62%), penyimpangan maksim penghargaan sebanyak 46 data (33,3%), penyimpangan maksim kesederhanaan sebanyak 26 data (18,84%), penyimpangan maksim permufakatan sebanyak 61 data (44,3%), dan penyimpangan maksim kesimpatisan sebanyak 17 data (12,6%). Selanjutnya didapatkan skala kesantunan sebanyak 209 pasangan ujaran. 138 memenuhi kesantunan dan 71 pasangan ujaran memenuhi ketidaksantunan. Hasil penelitian ini disimpulkan bahwa penyimpangan maksim kesantunan berbahasa lebih banyak dibandingkan dengan pemenuhan maksim kesantunan pada film kartun Spongebob Squarepants. Pada penelitian ini dapat diimplikasikan terhadap pembelajaran bahasa Indonesia, yaitu pembelajaran dalam teks diskusi kelas IX SMP. Kata kunci: maksim kesantunan, kartun, Spongebob Squarepants